2020
DOI: 10.1002/jsfa.10188
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil/lycopene microcapsules as a source of eicosapentaenoic and docosahexaenoic acids: a case study on spreads

Abstract: BACKGROUND The consumption of omega‐3 fatty acids has many beneficial effects for human health, but the intake of foods rich in these fatty acids is not enough to achieve the recommended quantity per person and per day, and their direct addition in foods cause oxidation and unacceptable rancidity and off‐flavor. Taking account of all these aspects, this study was aimed to develop stable microcapsules of fish oil (omega‐3 polyunsaturated fatty acids) and lycopene (antioxidant) and to investigate their effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Due to the high demand, PUFA-fortified products are widely available worldwide. Products fortified with fish, krill, and algal oils are popular due to their functionalities [ 98 , 99 ]. Given the oxidative vulnerability of PUFAs, different strategies are necessary to extend their shelf life.…”
Section: Fish By-products As a Source Of Various Bioactive Compoundsmentioning
confidence: 99%
“…Due to the high demand, PUFA-fortified products are widely available worldwide. Products fortified with fish, krill, and algal oils are popular due to their functionalities [ 98 , 99 ]. Given the oxidative vulnerability of PUFAs, different strategies are necessary to extend their shelf life.…”
Section: Fish By-products As a Source Of Various Bioactive Compoundsmentioning
confidence: 99%
“…Yeşilsu and Özyurt [ 46 ] evaluated the addition of rosemary, thyme and laurel extracts to a previously formed emulsion of anchovy oil with lactose and sodium caseinate, the highest oxidative stability being found in microcapsules with incorporated rosemary and laurel. In the study of Solomando et al [ 47 ], fish oil was mixed with lycopene and microencapsulated by using lecithin and maltodextrin. These authors reported a significant decrease in lipid oxidation markers as the lycopene content increased.…”
Section: Constituents Of Emulsions/solutions For Microencapsulationmentioning
confidence: 99%
“…The influence of the addition of ω-3 PUFA microcapsules to meat products has been preferably evaluated by means of the percentage of fat and fatty acids, lipid oxidation and acceptability analyses [30][31][32][33], paying less attention to the effect on the profile of volatile compounds, which may be related to the sensory attributes and/or have harmful effects, or its changes during the processing or storing.…”
Section: Introductionmentioning
confidence: 99%